Strontium-doped hydroxyapatite nanopowder via sol-gel method : effect of strontium concentration and calcination temperature on phase behavior - C. M., Mardziah; Iis, Sopyan; Ramesh, Singh (Society for Biomaterials and Artificial Organs - India, 2009)
Strontium doped hydroxyapatite (Sr-doped HA) nanopowder has been synthesized using a sol-gel method. The concentration of strontium was varied at 2, 5, 10 and 15 mol%. The as synthesized powders were calcined at temperatures of 500 -900ºC. The calcined white Sr-doped HA powders were characterized using differential and thermogravimetric analysis (TG/DTA), field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Morphological evaluation by FESEM measurement shows that the particles of the Sr-doped HA agglomerates are globular in shape with an average size of 1-2 mm in diameter while the primary particles have a diameter of 30-150 nm in average. The calcined powders contained hydroxyapatite phase only for all doping concentration except for the smallest doping concentration, 2 mol%, where â-TCP appeared as the secondary phase. This indicates that the substitution of Sr atoms for Ca atoms have stabilized the HA phase, leading to the inhibition of the appearance of â-TCP phase upon high temperature calcination. Even, for 2 mol% Sr-doped HA, the appearance of â-TCP peak only started to appear at a temperature as high as of 900ˆC, compared to non- Sr doping HA which appeared at a temperature below 800ºC. © Society for Biomaterials and Artificial Organs (India), 20090119-37